Desain Pendidikan Akhlak di Sekolah Menengah Pertama 2 Jember - Royani, Ahmad (Institut Agama Islam Negeri (IAIN) Curup, 2018)
The emergence of the counter-productive in the world of education has led to the emergence of symptoms among the youths, even the adults, which show that they ignore the moral values and manners needed in a civilized society. Concerns about moral decadence, it is like a double-edged knife. If you are looking for the root of the problem on others, it is essentially be the root of the problem of yourself; so, blaming others means also blaming themselves. Thus, it is necessary to find the solution and the moral education in an appropriate action. This research on